2004
DOI: 10.1097/01.alc.0000125356.70824.81
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moderate Alcohol Consumption on Plasma Dehydroepiandrosterone Sulfate, Testosterone, and Estradiol Levels in Middle‐Aged Men and Postmenopausal Women: A Diet‐Controlled Intervention Study

Abstract: Background: Moderate alcohol consumption is inversely associated with cardiovascular diseases. Changes in hormone levels might in part help explain the positive health effect. This study was performed to examine the effect of moderate alcohol consumption on plasma dehydroepiandrosterone sulfate (DHEAS), testosterone, and estradiol levels.Methods: In a randomized, diet-controlled, crossover study, 10 middle-aged men and 9 postmenopausal women, all apparently healthy, nonsmoking, and moderate alcohol drinkers, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 65 publications
(60 reference statements)
4
49
0
1
Order By: Relevance
“…However, observational data (Field et al 1994;Kiechl et al 2000;Ravaglia et al 2002), as well as two long-term, dietcontrolled intervention studies in pre-and postmenopausal women (Dorgan et al 2001;Reichman et al 1993) showed increased plasma DHEA-S concentrations after moderate alcohol consumption. Similarly, recent reports in postmenopausal women and middle-aged men show that individuals with higher levels of alcohol consumption have higher DHEA-S concentrations (Onland-Moret et al 2005;Mahabir et al 2004;Sierksma et al 2004).…”
Section: Introductionmentioning
confidence: 70%
“…However, observational data (Field et al 1994;Kiechl et al 2000;Ravaglia et al 2002), as well as two long-term, dietcontrolled intervention studies in pre-and postmenopausal women (Dorgan et al 2001;Reichman et al 1993) showed increased plasma DHEA-S concentrations after moderate alcohol consumption. Similarly, recent reports in postmenopausal women and middle-aged men show that individuals with higher levels of alcohol consumption have higher DHEA-S concentrations (Onland-Moret et al 2005;Mahabir et al 2004;Sierksma et al 2004).…”
Section: Introductionmentioning
confidence: 70%
“…In relation to this latter observation, it is interesting to note that in the absence of ethanol oestrogenic activity of wine extracts has been demonstrated (Klinge et al 2003) while that of beer, for example, appears to be minimal (Promberger et al 2001). Furthermore, Henk Hendrik's group (Sierksma et al 2004) have shown in a carefully-controlled intervention study that beer ingestion for 3 weeks in men and post-menopausal women (30 g ethanol/d) has no effect on plasma oestradiol levels. Further work is therefore required to determine whether wine drinking may differ in this respect, because of some non-ethanol components.…”
Section: Oestrogenic Effects Of Alcohol: Any Relevance To Bone Mineramentioning
confidence: 96%
“…In post-menopausal women or in men, who have lower natural levels of oestradiol than premenopausal women, the evidence for an effect of moderate alcohol ingestion is more limited. While the majority of studies show no effect of alcohol on oestradiol levels (Ginsburg et al 1996;Ginsburg, 1999;Sierksma et al 2004), the two studies that do show an effect for post-menopausal women are either inconsistent amongst their subgroups (Purohit, 1998) or suggest beverage specificity (i.e. positive for wine but not other beverages; Purohit, 1998).…”
Section: Oestrogenic Effects Of Alcohol: Any Relevance To Bone Mineramentioning
confidence: 99%
“…FTI did not differ between vegan and meat-eaters in any of the three studies. Furthermore, smoking has been related to elevated T and SHBG, both by survey (Allen et al, 2002;Svartzberg et al, 2003) and experimentally (English et al, 2001), while Sierksma et al (2004) report a small reduction in T with moderate alcohol consumption.…”
Section: Other Possible Factors Related To Hormonal Statusmentioning
confidence: 99%